Pemaknaan Kenosis sebagai Motivasi untuk Menghidupi Kekristenan yang Otentik di Era Postmodern - Donny Ardo Eka Dharma Putra Walui; Martina Novalina (Vox Dei: Jurnal Teologi dan Pastoral, 2024)
The postmodern era is characterized by a decadence of moral and spiritual values, including in Christian life. Many Christians lose their understanding of the true meaning of Christianity, which has an impact on behavior, moral values, and lifestyles that are contrary to the example of Jesus Christ. Church leaders tend to seek personal gain, avoid sacrifice, and serve with the wrong motivations. The Church of God is also often trapped in sin, unable to forgive, and views Christianity as a mere religion or routine. In this context, an understanding of kenosis—the self-emptying of Jesus Christ—can be a motivation to live authentic Christianity. Through a literature study with a qualitative approach, this study found that Jesus' kenosis that emphasizes obedience to God is an example for Christians to live according to His will. The meaning of kenosis invites Christians to abandon selfishness, live in holiness, and reflect the love of Christ in daily behavior. Thus, kenosis can be a spiritual foundation to restore the authenticity of Christian life in the postmodern era.